STRATEGI KOMUNIKASI PEMASARAN EFEKTIF @GOTBEEF.ID MELALUI MEDIA SOSIAL INSTAGRAM - Neema Aliifah Azzahra; Ratih Hasanah Sudradjat (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) AMIK Indonesia, 2023)
This study focuses on the effective marketing communication strategies of Got Beef Restaurant through the social media platform Instagram. The study analyzes the planning, implementation, and evaluation stages of the marketing communication strategy. The research findings reveal that Got Beef strategically determines market segmentation based on geographical, demographic, psychographic, and learning method factors. The target market consists of young people and women interested in the culinary experiences, especially burgers. Got Beef's positioning is related to the theme of feminism, aiming to differentiate itself from competitors and build a strong brand image. In terms of implementation, the message strategy used by Got Beef is persuasive, employing informal language and visually appealing content to engage with the audience. Instagram is chosen as the main communication medium due to its popularity and reach. The evaluation stage assesses the cognitive, affective, and conative effects on consumers by measuring understanding, emotional connection, and actions taken. This study suggests improvements in message clarity, focus on Instagram reels features, and the recruitment of social media or digital marketing experts. Overall, this study provides insights into the effective marketing communication strategies of Got Beef and highlights areas that need improvement.